2010
DOI: 10.1370/afm.1077
|View full text |Cite
|
Sign up to set email alerts
|

Health Extension in New Mexico: An Academic Health Center and the Social Determinants of Disease

Abstract: The Agricultural Cooperative Extension Service model offers academic health centers methodologies for community engagement that can address the social determinants of disease. The University of New Mexico Health Sciences Center developed Health Extension Rural Offi ces (HEROs) as a vehicle for its model of health extension. Health extension agents are located in rural communities across the state and are supported by regional coordinators and the Offi ce of the Vice President for Community Health at the Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 13 publications
0
41
0
Order By: Relevance
“…Summit participants examined roadmaps for transforming primary care practices with team-based approaches. Examples highlighted included the 10 Building Blocks of High-Performing Primary Care, 29 team strategies for integrating behavioral health and primary care, 30 incorporating patients and communi-ties into primary care teams (eg, community health workers), 31 and approaches for increasing joy in practice. 32 Participants concluded that effective teams must be adaptable with regard to the needs of the population, size of the community, and specific roles of team members.…”
Section: ) Team-based Care: Revisiting and Revitalizing Old Modelsmentioning
confidence: 99%
“…Summit participants examined roadmaps for transforming primary care practices with team-based approaches. Examples highlighted included the 10 Building Blocks of High-Performing Primary Care, 29 team strategies for integrating behavioral health and primary care, 30 incorporating patients and communi-ties into primary care teams (eg, community health workers), 31 and approaches for increasing joy in practice. 32 Participants concluded that effective teams must be adaptable with regard to the needs of the population, size of the community, and specific roles of team members.…”
Section: ) Team-based Care: Revisiting and Revitalizing Old Modelsmentioning
confidence: 99%
“…[14][15][16][17][18] Another PCEP prototype that has placed particular emphasis on a population health framework is the Health Extension Rural Offi ce (HERO) program coordinated by the University of New Mexico. 19 The HERO program partners with communities in every county of the state, identifying community health needs and mobilizing academic health center resources to meet those needs. HERO has trained and deployed community health workers to areas of need in support of primary care practices.…”
Section: Evidencementioning
confidence: 99%
“…29 This funding would support strategic training partnerships that help draw health professions students from underserved areas and return them there for portions of their training to build and reinforce relationships that help them choose to return home for their careers. The other aspect of this funding would support trainee participation in communityoriented primary care projects to include community defi nition, characterization, engagement, intervention, and evaluation.…”
Section: T I T L E V Ii Funding a Nd Pr Im A Ry C A R Ementioning
confidence: 99%